Thermogram Based Indirect Thermographic Temperature Measurement of Reactive Power Compensation Capacitors - Arkadiusz Hulewicz; Krzysztof Dziarski; Łukasz Drużyński; Grzegorz Dombek (Energies, 2023)
An increase in reactive power consumption results in an increase in electricity costs. This negative phenomenon can be prevented by using reactive power compensation methods. One of them is the installation of capacitors. These capacitors are exposed to external conditions, such as temperature and humidity. As a consequence, the aging process occurs. Another negative phenomenon is the corrosion that occurs inside the capacitor as a result of moisture absorption. As a result of this phenomenon, the capacitor can be damaged. One of the symptoms of the ongoing corrosion of the inside of the capacitor is an increase in temperature. Capacitors designed for reactive power compensation operate at mains voltage. They are often placed in a switchgear. For this reason, the use of contact methods of temperature measurement is difficult and dangerous. An alternative is thermographic measurement. Determining the internal temperature of the capacitor by thermographic measurement of the temperature of the case is possible with the use of numerical methods. One of them is FEM (Finite Element Method). The temperature results on the capacitor housing obtained from the simulation work were verified by comparing them with the result of thermographic temperature measurement. Both values differed by 0.2 °C. On the basis of the defined model, the differences between the temperature inside the capacitor housing and the temperature on the capacitor housing were determined by simulation. A simplification was proposed by replacing the cylinder made of layers with a homogeneous cylinder.